Study of Market Facilities in the Revitalization Project of Klewer Market - Yulia Pratiwi; Fadhilah Rusmiati (Departement of Architecture, Universitas Islam Indonesia, 2018)
Klewer Market is the largest clothing, textile, garment market in Central Java. Klewer Market was established in 1970 and in 2014 there was a fire so that in 2015 the Government of Surakarta City revitalized Klewer Market. In April 2017, Klewer Market has been revitalized and inaugurated. The purpose of this study is to understand the general description of the conditions, the completeness of facilities and utilities, and to investigate the improvement in the management of Klewer Market after revitalization. This research uses qualitative descriptive research to find out a general description of Klewer Market conditions after revitalization in terms of physical buildings, facilities, utilities and management. The analytical method uses a comparison of pre-revitalization market conditions with post-revitalization market conditions. The conclusion of this study is that Klewer Market post-revitalization has a more modern concept than pre-revitalization and is able to become one of tourist icons in Surakarta City, which already has more adequate facilities, utilities, and management.Keyword: Klewer Market, Revitalization, Facilities.